Assessment of Implant Stability Following Sinus Lift Procedures with Different Grafting Materials - Damir Jelušić; Ivan Puhar; Darije Plančak (University of Zagreb. School of Dental Medicine, 2014)
Objective: The objective of this research was to evaluate implant stability following sinus lift with two grafting materials, and to compare it with the results obtained for the implants placed in a pristine posterior maxilla. Materials and methods: The study included 44 healthy patients with an existing indication for sinus lift procedure (test group). 46 implants were placed following sinus lift with a pure-phase beta-tricalcium phosphate, while 39 implants were placed following augmentation with 60% hydroxyapatite with 40% beta-tricalcium phosphate material. The control group consisted of 48 healthy patients who were treated with 85 implants but without bone augmentation in posterior maxilla. Astra Tech OsseoSpeed implants were placed in all subjects. Resonance frequency analysis was used in both groups for determining implant stability 4 months after insertion. A mean implant stability quotient (ISQ) was calculated on the basis of 3 measurements. Results: No statistical difference was observed in ISQ values of implants placed with and without augmentation procedure (p=0,789). Statistically significant difference was not found when ISQ values of implants placed following particular grafting material were compared with ISQ values of corresponding implants in a pristine bone (p=0.697 and p=0.402). Conclusions: This study demonstrated that the implant stability is comparable among implants placed in the posterior maxilla regardless of sinus lift and grafting procedure. Implants placed in the grafted posterior maxilla can be predictably loaded as the implants placed in a non-grafted, pristine maxilla.